SOIL CONSERVATION PROGRAMNIE FOR THE FRAGILE ECO-CATTERING TO THE FUEL NEEDS OF WATERSHED PEOPLE THROUGH ENERGY PLANTATION IN THE COMMUNITY WASTE LAND IN THE FRAGILE BANK OF TILAIYA RESERVOIR - Misra, K.; Basu, P.K. (Journal of Soil and Water Conservation, 2022)
With ever increasing attention being focused worldwide on forestry in general and community forestry in particular, there is a need to encourage large scale afforestation programme in the degraded community waste land. Village Dhabsolonia in Kodarma District having vast area of community waste land in the fragile hank of Tilaiya reservoir. Therefore, there is a vast scope for development of this land and bring this fragile eco-system to put into production use. Soil Cons. Department. DVC, Hazaribagh was taken the energy plantation programme as integrated watershed development project at Dhabsolonia in Kodarma District. 356 ha. of waste land was tackled from 1993 to 1996 under energy plantation programme. The work has been evaluated by the Author as the success of the plantation and as the benefit drawing by the villagers from this afforestation programme. Out of the area evaluated about 75 per cent area planted was found to be good to very good and 30 per cent of the total household are getting complete benefit from this forest.